2023
DOI: 10.36227/techrxiv.170327806.66007684/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Harmonia: Securing Cross-Chain Applications Using Zero-Knowledge Proofs

Rafael Belchior,
Dimo Dimov,
Zahary Karadjov
et al.

Abstract: The field of blockchain interoperability plays a pivotal role in blockchain adoption. Despite these advances, a notorious problem persists: the high number and success rate of attacks on blockchain bridges. We propose Harmonia, a framework for building robust, secure, efficient, and decentralized cross-chain applications. A main component of Harmonia is DendrETH, a decentralized and efficient zero-knowledge proof-based light client. DendrETH mitigates security problems by lowering the attack surface by relying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…The authors used zkp to prove (in Ethereum) the existence of a block committed in Cosmos, and we used them to prove the existence of permissioned data in Fabric. However, the authors' costs analysis showed that block validation can cost 0.3 dollars, which gives 2136,6 dollars per day 5 . These results are aligned with our results as zkp are yet expensive to be used in real-world scenarios.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors used zkp to prove (in Ethereum) the existence of a block committed in Cosmos, and we used them to prove the existence of permissioned data in Fabric. However, the authors' costs analysis showed that block validation can cost 0.3 dollars, which gives 2136,6 dollars per day 5 . These results are aligned with our results as zkp are yet expensive to be used in real-world scenarios.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Belchior et al [5] proposed Harmonia, a framework to build cross-chain applications. One of its components is DendrETH, a decentralised zero-knowledge proof-based light client that prevents the Ghost Checkpoint Attestation Attack.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation